Circular Economy Implementation in Water Hyacinth Craft SMEs for Sustainable Business - Utaminingsih, Adijati; Lestari, Rohmini Indah; Rahoyo, Stefanus; Widyasmara, Bobby (Pandawan, 2026)
This study examines the application of a green business model based on circular economy principles to water hyacinth craft micro, small, and medium enterprises (MSMEs) in Central Java, Indonesia. Environmental concerns continue to rise and the traditional craft industry has the potential for sustainable transformation. However, empirical studies on the influence of green business models on the competitiveness of MSMEs in the context of developing countries are still limited. The researchers used Smart Partial Least Squares Structural Equation Model 4.0 (Smart-PLS 4.0) to analyse data from 148 water hyacinth craft MSMEs in Demak, Semarang, and Sukoharjo Regencies. The results show that green business models significantly enhance the sustainable competitiveness of MSMEs through three key mediators: green entrepreneurial orientation, environmentally friendly collaboration, and green innovation. Green innovation is the most crucial mediator linking sustainability orientation to competitive advantage. In contrast, government policy support does not significantly moderate this relationship, indicating a gap between policy instruments and the reality of MSMEs. These findings enrich the theory of sustainable business models by demonstrating the circular economy mechanisms of resource-constrained MSMEs. Practically, this study provides insights for MSME practitioners and policymakers in developing countries to integrate environmental sustainability and business viability.